Inspiratory Strength and Diaphragm Thickness in Tennis Players with and Without Non-Specific Shoulder Pain - Davinia Vicente-Campos; Jorge Sánchez-Infante; César Calvo-Lobo; David Rodríguez-Sanz; Ricardo Becerro-de-Bengoa-Vallejo; José López-Chicharro; Iñaki Quintana (Journal of Clinical Medicine, 2026)
Background/Objectives: Shoulder pain in tennis players is usually interpreted from a local shoulder perspective, although kinetic-chain and trunk-control factors may also be relevant. The diaphragm contributes to breathing and trunk stabilization, but diaphragm-related measures have received limited attention in tennis players with shoulder pain. This study compared inspiratory muscle strength, diaphragm thickness, and diaphragm thickening fraction between tennis players with and without non-specific shoulder pain. Methods: This observational cross-sectional study included 64 tennis players: 32 with non-specific shoulder pain and 32 asymptomatic controls. Maximum inspiratory pressure (MIP), bilateral diaphragm thickness during relaxed inspiration and expiration, and diaphragm thickening fraction were assessed. Between-group differences were analyzed. Results: Tennis players with non-specific shoulder pain showed lower MIP than controls (p = 0.002). Diaphragm thickness during relaxed inspiration was lower in symptomatic players on the left (false discovery rate (FDR)-adjusted p = 0.033) and right sides (FDR-adjusted p = 0.012), and diaphragm thickening fraction was also lower bilaterally (left: FDR-adjusted p = 0.036; right: FDR-adjusted p = 0.039). Conclusions: Tennis players with non-specific shoulder pain showed lower inspiratory muscle strength, lower bilateral diaphragm thickness during relaxed inspiration, and lower bilateral diaphragm thickening fraction than asymptomatic players. These cross-sectional findings describe group-level differences but do not establish causality, diaphragm dysfunction, or clinical relevance.